Sexual Harassment in Public Transport and its Coping Strategies among Bachelor Level Students: A Cross Sectional study - Adhikari, Rubina; Sah, Bimlesh; Subedi, Prativa; Thapaliya, Pooja; Panthi, Laxmi; Baniya, Ambika (Journal of Karnali Academy of Health Sciences, 2020)
Introduction: Sexual harassment in public transport is a common, yet little discussed form of gender-based aggression, predominantly to women. Such abuses have significant on the mental health of the victims. It also leads them to abandon work and education due to the fear of being harassed on their route. Knowledge regarding the prevalence and coping strategies against such harassment is necessary to formulate effective plans for its mitigation.Methods: This was a cross sectional study done among 105 bachelor students of Maiya Devi Kanya College of Bharatpur, Chitwan via convenience sampling. Self-administered structured questionnaires were used. Data was analyzed using descriptive statistics (frequency, percentage). Chi square test was used to determine the association between variables.Results: Almost half (50.5%) respondents had seen other girls being harassed while 21.9 % students mentioned that they had themselves been sexually harassed in public transport. Most common form of harassment seen was verbal while most common harassment faced was non-verbal followed by verbal and physical. Harassment was more during morning (52.17%) and evening hours (32.78%). Almost half of the respondents mentioned that they would prefer to remain silent (47.6 %) and not react to the situation (54.3%). Self-discipline (66.7%) and effective law (65.7%) were deemed as major ways to prevent such abuses by most of the respondents. Conclusion: Verbal harassment is the most common form of harassment seen and non-verbal harassment is the commonest form experienced in public transport. Such harassments usually occur during peak hours where vehicles are congested. As majority of the respondents preferred to remain silent to the situation, what is evident represents only the tip of iceberg. Strict laws were deemed necessary by the respondents necessary to curtail this problem.